Pemanfaatan Daun Kelor (Moringa oleifera) menjadi Olahan Makanan yang Bergizi - Parera, Lolita A. M.; Jasman, -; Budiana, I Gusti M. N.; Sarifudin, Kasimir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Nusa Cendana, 2021)
Abstract - Seki Village is a dry land area in the East Nusa Tenggara region where the majority of the population work as farmers. Moringa plants are easy to grow in dry land areas, so they are widely available in Seki village. Scientifically, Moringa that grows in dry land areas in NTT has a higher nutrient content than those found elsewhere. At the time of the survey in the partner area, namely the homes of residents in Seki Village, it was stated that this plant lives very much and is abundant. The problem occurs when the abundant moringa plant is only processed in the form of boiled vegetables so that on average it is disliked by children and adults who consume it. However, if it is processed in an innovative way, it will increase people's interest in consuming it and can improve the economy of the people. This Program of devotion is implemented to provide alternative solutions. External to be achieved: 1) Increased community motivation to be more productive and creative in managing Moringa leaves, 2) Knowing science and technology to produce noodles and cakes made from Moringa leaves, 3) Skilled in making noodles and cakes made from moringa Moringa leaves, 4) Increased business opportunity reference for the people of Seki Village. The program partners are local women who are members of the Ebenhazer Congregation. The program ran smoothly and received support from church leadership. The results obtained 1) This service has a positive impact on the community by introducing the technology of making noodles and cakes made from Moringa leaves as an alternative for consuming Moringa leaves, 2) This program provides skills to partner groups regarding the ways and steps of making noodles and cakes made from moringa Moringa leaves which have the potential as a home industry, 3) still need special attention from various parties to improve the Village Human Resources Seki in maximizing the potential of Moringa leaves. The method used is through a workshop, namely the provision of material and practice of making noodles and cakes made from Moringa leaves by the participants in the activity. Abstrak – Desa Seki merupakan daerah lahan kering di wilayah nusa tenggara timur yang mayoritas penduduknya berprofesi sebagai petani. Tanaman kelor merupakan yang mudah tumbuh di daerah lahan kering sehingga banyak terdapat di desa Seki. Secara ilmiah, kelor yang tumbuh di daerah lahan kering di NTT mempunyai kandungan gizi lebih tinggi dari kandungan gizi yang hidup di tempat lain. Pada saat survei di daerah mitra yaitu rumah warga di Desa Seki bahwa tanaman ini hidup sangat banyak dan melimpah. Masalah terjadi ketika tanaman kelor yang melimpah hanya diolah dalam bentuk sayur yang direbus sehingga rata-rata tidak disukai oleh anak-anak dan orang dewasa yang mengkonsumsinya. Namun bila didiolah secara inovatif maka akan menambah minat masyarakat dalam mengonsumsinya dan dapat meningkatkan perekeonomian warga. Program pengabdian ini dilaksanakan untuk memberikan solusi alternatif yang ingin dicapai yaitu: 1) Meningkatnya motivasi masyarakat untuk lebih produktif dan kreatif dalam mengelola daun kelor, 2) Mengetahui IPTEK memproduksi mie dan kue berbahan dasar daun kelor, 3) Terampil membuat mie dan kue berbahan dasar daun kelor, 4) Meningkatnya referensi peluang usaha bagi masyarakat Desa Seki. Mitra program adalah para ibu-ibu warga sekitar yang tergabung dalam Jemaat Ebenhazer. Program berjalan dengan lancar dan mendapat dukungan dari pimpinan jemaat. Hasil yang diperoleh 1) Pengabdian ini berdampak positif bagi masyarakat dengan memperkenalkan teknologi pembuatan mie dan kue berbahan dasar daun kelor sebagai salah satu alternatif dalam mengkomsumsi daun kelor, 2) Program ini memberikan ketrampilan kepada kelompok mitra terkait cara dan langkah pembuatan mie dan kue berbahan dasar daun kelor yang berpotensi sebagai industri rumah tangga, 3) masih perlu perhatian khusus dari berbagai pihak untuk meningkatkan SDM Desa seki dalam memaksimalkan potensi daun kelor. Metode yang digunakan adalah melalui kegiatan workshop yakni pemberian materi dan praktik membuat mie dan kue berbahan dasar daun kelor oleh peserta kegiatan